Risk factors for atrioventricular block after transcatheter aortic valve implantation: a single-centre analysis including assessment of aortic calcifications and follow-up. Issue 5 (9th January 2019) - Pollari, Francesco; Großmann, Irena; Vogt, Ferdinand; Kalisnik, Jurij Matija; Cuomo, Michela; Schwab, Johannes; Fischlein, Theodor; Pfeiffer, Steffen
Abstract: Aims: To assess the contribution of aortic valve calcification to the occurrence of transient or permanent atrioventricular block (AVB) and the need for permanent pacemaker implantation (PPI) after transcatheter aortic valve implantation (TAVI) in a large single-centre cohort. Methods and results: We retrospectively analysed pre-operative contrast-enhanced multidetector computed tomography scans of patients who underwent TAVI in our centre between 2012 and 2016. Calcium volume was calculated for each aortic cusp above (aortic valve), and below [left ventricular outflow tract (LVOT)] the basal plane. Clinical and procedural data as well as pre-operative electrocardiograms were evaluated. Multivariate analysis was performed to evaluate risk factors for transient and permanent AVB. A total of 342 patients receiving a balloon-expandable prosthesis were included in the study. Overall incidence of transient and permanent AVB was 4% ( n = 14) and 7.6% ( n = 26), respectively. On logistic regression analysis, baseline right bundle branch block [odds ratio (OR) 7.36, 95% confidence interval (CI) 2.6–20.6; P < 0.01], degree of oversizing (OR 1.04, 95% CI 1.01–1.07 P = 0.02), prior percutaneous coronary intervention (OR 2.8, 95% CI 1.1–7.3), and LVOT calcification beneath the non-coronary cusp (OR for an increase of 10 mm 3 = 1.06, 95% CI 1–1.1; P = 0.03) were found to be independently associated with permanent AVB and PPI, whereas calcification of LVOT beneath the right coronary cusp (OR for an increase of 10 mm 3 = 1.16, 95% CI 1.02–1.3; P = 0.02) and balloon post-dilation (OR 3.8, 95% CI 1.2–11.8; P = 0.02) were associated with reversible AVB. Conclusion: Left ventricular outflow tract calcifications are associated with transient and non-reversible AVB after TAVI, and its evaluation could help in predicting onset and reversibility of AVB.